Design of a Solar Motor Drive System Fed by a Direct-Connected Photovoltaic Array - Aydogmus, Omur (Univ Suceava, Fac Electrical Eng, 2012)
A solar motor pump drive system is modeled and simulated. The proposed drive system does not require any kind of energy storage system and dc-dc converter. The system is connected directly to a photovoltaic (PV) array. Thus, a low cost solar system can be achieved. A vector controlled Permanent Magnet Synchronous Motor (PMSM) is used as a solar motor to increase the efficiency of system. The motor is designed for a low rated voltage level about 24V. The hill climbing MPPT method is used for balanced the motor power and PV power to obtain a high efficiency. The results are performed by using MATLAB/SimPowerSystem blocks. In addition, the PV array is modeled to allow for the possibility of running as on-line adjustable in simulation environment without using lookup table. The performances of motor, MPPT and drive system are analyzed in different conditions as temperature and irradiation of PV array.
Keywords: maximum-power-point-tracking method; permanent magnet motor; photovoltaic systems; solar power generation; space vector PWM